For-Profit Public Intellectuals. (November 2014) - Pilgeram, Ryanne; Meeuf, Russell
Sociologist Ryanne Pilgeram and media scholar Russell Meeuf discuss the hijacking of public debate by private research organizations, using the viral video "The Economics as Sex" as an example.